2019
DOI: 10.1016/j.ymthe.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

A Stem Cell-Based Screening Platform Identifies Compounds that Desensitize Motor Neurons to Endoplasmic Reticulum Stress

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease selectively targeting motor neurons in the brain and spinal cord. The reasons for differential motor neuron susceptibility remain elusive. We developed a stem cell-based motor neuron assay to study cell-autonomous mechanisms causing motor neuron degeneration, with implications for ALS. A small-molecule screen identified cyclopiazonic acid (CPA) as a stressor to which stem cell-derived motor neurons were more sensitive than interneurons. CPA ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 100 publications
(147 reference statements)
4
42
0
Order By: Relevance
“…CPA blocks sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA), the Ca 2+ -pump in endoplasmic reticulum (ER) membrane that helps to maintain Ca 2+ balance and ER homeostasis, and thus has a broader effect. Notably, CPA was reported to accelerate the degeneration of SpMNs expressing hSOD1 G93A mutant, suggesting that CPA treatment may reveal ALS-relevant differential vulnerability between iCrMNs and iSpMNs (Thams et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…CPA blocks sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA), the Ca 2+ -pump in endoplasmic reticulum (ER) membrane that helps to maintain Ca 2+ balance and ER homeostasis, and thus has a broader effect. Notably, CPA was reported to accelerate the degeneration of SpMNs expressing hSOD1 G93A mutant, suggesting that CPA treatment may reveal ALS-relevant differential vulnerability between iCrMNs and iSpMNs (Thams et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…However, neither genetic inhibition of the UPR via ablation of PERK, nor genetic UPR enhancement via ablation of GADD34, had a beneficial effect in mutant SOD1 mice (Dzhashiashvili et al, 2019 ). More recent studies in SOD1-iPSC and mouse models demonstrated that MNs are more sensitive to ER stress and identified a number of modifiers, including TUDCA, a bile acid derivative which is currently undergoing clinical trials in ALS (Thams et al, 2019 ; Paganoni et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of microtubule mass or altered microtubule dynamics in axons and dendrites are major contributors to neurodegenerative diseases such as ALS, Parkinson's disease, Alzheimer's disease, and several tauopathies (59). A recent screen of a ~100 small molecules identified compounds protective of ER stress in a chemicallyinduced ER stress model of ALS (SOD1 G93A ) neurodegeneration (60). Future studies will determine whether compounds that affect microtubule dynamics are able to prevent disease-relevant phenotypes in cellular models of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%